Nanobiosensors: Concepts and Emerging Clinical Applications - Desai, Sagar; Naveen, Raghavendra R.; Goudanavar, Prakash S; Gowthami, Buduru (Pharmaceutical Nanotechnology, 2024)
Biosensors have been one of the most fascinating topics for scientists for a long time. This is because biological moieties are multifaceted and are unswervingly related to the presence of a healthy atmosphere. The biosensor approach has also endured profound changes in recent years. Biosensors have been emphasized for various applications, including food quality estimation, surveillance systems, and health and metabolic abnormality diagnostics. The advances in nanotechnology have led to a considerable potential to enhance biosensors' sensitivity, robustness, and anti-interference capabilities. Several new nanomaterials (such as nanoparticles, nanotubes, nanorods, and nanowires) have been fabricated due to the evolution of nanotechnology, and their unique features are gradually being identified, allowing for much faster detection and reproducibility. Biosensor performance has also been enhanced substantially as a result of their use. Because of their capacity to detect a wide range of compounds at deficient concentrations, nanobiosensors have sparked much interest. This article discusses biosensors based on various nanomaterials, their evolution, accompanying features, and their applications in multiple fields.
Keywords: nanoparticles